On a New Sustainable Energy Policy: Exploring a Macro-Meso-Micro Synthesis - Dimos Chatzinikolaou; Charis Michael Vlados (Energies)
This study examines the differences between the emerging new energy policy and its predecessor, offering guidelines for an integrated approach to support a rapid and sustainable energy transition. Using a bibliometric and qualitative integrative analysis of 360 scientific articles on energy policy, ecosystems, and entrepreneurship—supplemented by insights from 16 experts in the European energy sector and an in-depth analysis of 89 relevant business cases—this research identifies a significant shift in priorities. Traditional concerns, such as energy security, self-sufficiency, and market liberalization, are increasingly giving way to a focus on rapid, sustainable energy transitions and development at the macrolevel. The findings reveal that contemporary energy policies are progressively prioritizing integrated strategies across the macrolevel, mesolevel, and microlevel. At the macrolevel, policies are increasingly focused on enabling efficient transitions and promoting sustainable development within an ecosystemic framework. At the mesolevel, there is a growing emphasis on strengthening regional energy ecosystems. At the microlevel, the focus increasingly shifts toward empowering energy firms through innovative organizational strategies, technological advancements, and enhanced managerial practices. The proposed integrated energy policy aims to address these broader goals while fostering diverse energy ecosystems and communities at the mesolevel. Additionally, it emphasizes the importance of empowering individual energy firms by enhancing their strategies, technological capabilities, and managerial skills. These improvements are essential for driving innovation, developing green business models, strengthening corporate social responsibility, and aligning with the principles of Resilience, Adaptability, Sustainability, and Inclusiveness (RASI).